2014
DOI: 10.1080/10615806.2014.925545
|View full text |Cite
|
Sign up to set email alerts
|

Executive function moderates the relation between coping and depressive symptoms

Abstract: Background and Objectives Identifying risk factors early in the course of depression has important implications for prevention, given that the likelihood of recurrence increases with each successive episode. Design This study examined relations among coping, executive functioning, and depressive symptom trajectories in a sample of remitted-depressed (n = 32) and never-depressed (n = 36) young adults (ages 18 to 31). Methods Participants completed a clinical interview, a measure of coping, and tasks assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 52 publications
2
23
0
1
Order By: Relevance
“…In our study sample, scores on the CES-D were associated with avoidant coping strategies, and, more specifically, the participants with lower scores on the CES-D showed less use of avoidance strategies. In this vein, the findings of Morris et al. (2015) suggest that lower inhibitory capacity and less use of primary control coping 1 were associated with lower depressive symptoms at baseline but predicted increases in depressive symptoms at follow-up.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In our study sample, scores on the CES-D were associated with avoidant coping strategies, and, more specifically, the participants with lower scores on the CES-D showed less use of avoidance strategies. In this vein, the findings of Morris et al. (2015) suggest that lower inhibitory capacity and less use of primary control coping 1 were associated with lower depressive symptoms at baseline but predicted increases in depressive symptoms at follow-up.…”
Section: Discussionmentioning
confidence: 92%
“…According to Gotlib and Joorman (2010), inhibitory deficits might increase the risk of depression, as they reinforce negative affectivity (e.g., incapacity to disengage from negative stimuli or rumination). However, results in this regard are not conclusive because, although it has been suggested that inhibitory control might serve as a protective factor against depression, it has also been found that higher primary control and lower inhibition scores were not associated with increments in depression, that is, primary strategies such as PS could compensate for inhibitory deficits (Morris et al., 2015). WM has also been found to be related to secondary control coping 2 (Andreotti et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on shifting as a prospective predictor of depression is similarly sparse. Poorer shifting on a variety of tasks predicted the first onset of major depressive episodes among adolescents (Stange et al., ), a greater likelihood of depressive relapse (Schmid & Hammar, ), better response to psychotherapy for depression (Beaudreau et al., ), and fewer future symptoms of depression only in the context of better coping (Morris et al., ), supporting the hypothesis that individual differences in shifting could confer vulnerability to depression. In contrast, other studies of nonclinical samples have found that perseverative costs on the WCST were not associated with prospective symptoms of depression (Evans et al., 2016; Han et al., ).…”
Section: Theory and Evidence For Components Of Flexibilitymentioning
confidence: 89%
“…And, specific dimensions of EF such as cognitive rigidity (the opposite of cognitive flexibility) have been shown to be negatively related to both anxiety and depression (Kashdan & Rottenberg, 2010; Meiran, Diamond, Toder, & Nemets, 2011; Schultz & Searleman, 2002). Likewise, research studies have found that working memory (Andreotti et al, 2013), attentional control (Hocking et al, 2011), and inhibitory control (Morris et al, 2015) are significantly associated with anxiety and depression.…”
Section: The Relation Between Ef and Mental Healthmentioning
confidence: 99%